Perjanjian Sewa Menyewa Penempatan Pesawat Terbang Antara Maskapai Penerbangan Lion Air Dengan PT. Persero Angkasa Pura IICabang Bandara Sultan Thaha Jambi - Syarifa Mahila (Jurnal LEX SPECIALIS, 2011)
For air transport, aircraft owners want a parking space plane closest to the airport which is used for the implementation of its business operations or in the airport itself. Among the companies in Edinburgh who desperately need the aircraft parking facilities are airline Lion Air. Parties designated by the airline Lion Air for aircraft parking is PT. (Persero) Angkasa Pura II Jambi which manages  Jambi Sultan Taha Airport. The relationship between the airline Lion Air and PT. Persero Angkasa Pura II Jambi Sultan Taha Airport Branch tied into a written agreement with the name of the rental agreement aircraft placement. In the execution of lease agreement the placement of an aircraft which was held between the airline Lion Air and PT. Persero Angkasa Pura II Jambi Sultan Taha Airport Branch was not all goes smoothly, but there are encountered problems. Key Note : Rent Lease Agreemeent